ELECTROANALYSIS OF IBUPROFEN ON CONDUCTING POLYANILINE NANOFIBER COATED GLASSY CARBON SURFACE - Suresh, E.; Sundaram, K.; Kavitha, B.; Kumar, N. Senthil (International Journal of Current Pharmaceutical Research, 2016)
Objective: Voltammetric procedure for analysis of pharmaceutical formulation of ibuprofen on conducting polyaniline nanofiber modified glassy carbon electrode was explored. Methods: The effect of pH was studied at different medium such as acidic, neutral and basic. The cyclic voltammetric behavior of ibuprofen was studied betweenâˆ’0.5 V and 1.8 V versus Ag/AgCl at modified glassy carbon surface. Results: The electroanalytical parameters of the detection are highly dependent on their configuration and dimensions of the electrode. The scan rate and concentration effect of ibuprofen were studied. The best limit of detection was 100 ppb and the linear range from 200 to 400 ppb on the modified electrode surface. The determination was successfully applied for the detection of drugs in several pharmaceutical drug formulations. The Atomic force microscopic (AFM) image shows the surface morphologies of polymer modified surface; compound adsorbed surface, particle distribution graphs and surface roughness values, which are in good agreement. Conclusion: The anodic peak was observed at 1.63 V, assigned for the oxidation of ibuprofen, which is not accompanied by corresponding cathodic reduction. This behavior suggested that the irreversibility of the electrode process.